From Sidewalk to Subway : Achieving Sustainable Financing for Urban Transport - Ardila-Gomez, Arturo (World Bank, Washington, DC, 2016)
This brief talks about achieving sustainable financing for urban transport in developing countries. The state of urban travel in many developing countries is grim. Congestion and low-quality infrastructure, including limited network coverage and poor roads and sidewalks slow travel times, which slows economic development. Lower-income residents rely the most on public transport and bear a disproportionate share of the burden of its failures. The low quality of urban public transport systems in developing countries indicates a chronic financing gap, underfinancing for capital investments, operations, and maintenance. Though urbanization is an important ingredient in poverty reduction, it inevitably strains urban transport, so it is widening the financing gap. World Bank research released this year has pinpointed sources of the financing problem and proposed a response based on the concept of, "who beneﬁts, pays." By tapping into innovative revenue sources that promote efficient pricing, increase overall revenue, and strengthen all elements of sustainable transport, urban areas in developing countries can fund a wide variety of urban transport projects in a manner that will ensure their sustainability. To conclude, by combining appropriate financing instruments and focusing on the “Who benefits, pays” principle, overburdened urban transport systems can be revived with wise and sustainable investments to cover capital, operation and maintenance of all parts of a transport system,“from the sidewalk to the subway.”